Nanoscaled biphasic calcium phosphate modulates osteogenesis and attenuates LPS-induced inflammation - Su, Yi-Chun; Phan, Trinh T. T.; Wang, Tzu-Wei; Chang, Shao-Hsuan; Lin, Feng-Huei; Hsu, Tzu-Sheng; Lin, Lih-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Micron-scale structure biphasic calcium phosphate (BCP) materials have demonstrated promising clinical outcomes in the field of bone tissue repair. However, research on biphasic calcium phosphate materials at the nanoscale level remains limited. In this study, we synthesize granular-shaped biphasic calcium phosphate nanomaterials with multiple desirable characteristics, including negatively charged surfaces, non-cytotoxicity, and the capability to penetrate cells, using a nanogrinding dispersion process with a polymeric carboxylic acid as the dispersant. Our results reveal that treating human osteoblasts with 0.5 μg/mL biphasic calcium phosphate nanomaterials results in a marked increase in alkaline phosphatase (ALP) activity and the upregulation of osteogenesis-related genes. Furthermore, these biphasic calcium phosphate nanomaterials exhibit immunomodulatory properties. Treatment of THP-1-derived macrophages with BCP nanomaterials decreases the expression of various inflammatory genes. Biphasic calcium phosphate nanomaterials also mitigate the elevated inflammatory gene expression and protein production triggered by lipopolysaccharide (LPS) exposure in THP-1-derived macrophages. Notably, we observe that biphasic calcium phosphate nanomaterials have the capacity to reverse the detrimental effects of LPS-stimulated macrophage-conditioned medium on osteoblastic activity and mineralization. These findings underscore the potential utility of biphasic calcium phosphate nanomaterials in clinical settings for the repair and regeneration of bone tissue. In conclusion, this study highlights the material properties and positive effects of biphasic calcium phosphate nanomaterials on osteogenesis and immune regulation, opening a promising avenue for further research on inflammatory osteolysis in patients undergoing clinical surgery.